Role of international trade competitive advantage and corporate governance quality in predicting equity returns: Static and conditional model proposals for an emerging market - Erol Muzir; Cevdet Kizil; Burak Ceylan (Journal of Risk and Financial Management, 2021)
This paper aims to develop some static and conditional (dynamic) models to predict portfolio returns in the Borsa Istanbul (BIST) that are calibrated to combine the capital asset-pricing model (CAPM) and corporate governance quality. In our conditional model proposals, both the traditional CAPM (beta) coefficient and model constant are allowed to vary on a binary basis with any degradation or improvement in the country's international trade competitiveness, and meanwhile a new variable is added to the models to represent the portfolio's sensitivity to excess returns on the governance portfolio (BIST Governance) over the market. Some robust and Bayesian linear models have been derived using the monthly capital gains between December 2009 and December 2019 of four leading index portfolios. A crude measure is then introduced that we think can be used in assessing governance quality of portfolios. This is called governance quality score (GQS). Our robust regression findings suggest both superiority of conditional models assuming varying beta coefficients over static model proposals and significant impact of corporate governance quality on portfolio returns. The Bayesian model proposals, however, exhibited robust findings that favor the static model with fixed beta estimates and were lacking in supporting significance of corporate governance quality.
Keywords: G11; G12; G17; 330; Bayesian regression; Borsa Istanbul; corporate governance quality; international trade capability; robust linear regression; static and conditional asset-pricing models